STRATEGI KOMUNIKASI DINAS PARIWISATA KABUPATEN PALUTA DALAM PUBLIKASI OBJEK WISATA BARUMUN NAGARI - Risma Dona Siregar; Faisal Riza; Muhammad Faishal (PROGRAM STUDI ILMU KOMUNIKASI, 2022)
THE COMMUNICATION STRATEGY OF THE TOURISM SERVICE OF PALUTA REGENCY IN THE PUBLICATION OF BARUMUN NAGARI TOURISM OBJECTSRisma Dona Siregar(1)Faisal Riza(2)Muhammad Faishal(3)risma99dona@gmail.comNorth Sumatra State Islamic University, Faculty of Social Sciences, Jl. Field Golf, No. 120. Kp. Central, District. Pancur Batu, Deli Serdang Regency, North Sumatra ABSTRACTThe purpose of this study is to find out the strategies applied by the Paluta Government in the Publication of Barumun Nagari Tourism Objects. The research method used is descriptive research with a qualitative approach and presents problems that occur in the field by analyzing the Strategy of the Paluta Regency Tourism Office in the Publication of Barumun Nagari Tourism Objects. Data collection techniques using observation, interviews and documentation with Dramaturgy theory. The results of research at the Department of Culture and Tourism of North Padang Lawas Regency obtained that the strategy carried out in the publication of Barumun Nagari. indeed must pay attention to several aspects, among others, by implementing the goals and objectives, programs, and policies that will be made.